Enhancing cancer care through addressing a neglected pillar: a narrative review on quality of life in Pakistani patients - Taimoor Khalid Janjua; Amir, Saniya; Saad Ullah Khan; Zulfiqar, Fizza; Afridi, Hira Khan (Journal of the Pakistan Medical Association, 2024)
The current narrative review was planned to evaluate the quality of life of Pakistani cancer patients. Using relevant questionnaires and comparing global data over the last 2 decades, the review planned to explore artificial intelligence’s role in cancer care, and to develop strategies for better outcomes. The review yielded poor results and exposed huge and neglected gaps in the overall approach towards the management of cancer patients based on different tumour types and categories. A few experimental interventions demonstrated promising results and echoed the need for further clinical and non-clinical experimentation for negating poor quality of life outcomes. Unsurprisingly, not a single study in the literature analysed revealed a positive quality of life. A multi-pronged approach, therefore, must be brainstormed and safely implemented through experimentation of artificial intelligence and active coordination among healthcare bodies, finance/economic boards and welfare organisations that are active in countries like Pakistan to uplift the neglected quality of life domain among cancer patients, especially breast and oral cancers that have the highest incidences worldwide. Key Words: Quality of life, Neoplasms, Breast neoplasms, Mouth neoplasms.